The Impact of Globalisation on Income Inequality: A Comparative Analysis of Developed and Developing Countries - Arryan Sanjay Yadav (European Economic Letters (EEL), 2023)
The article analyses how globalization affects income inequalities over the world, by comparing developed and developing economies. Globalization has interconnected economies, and societies, worldwide through the free flow of capital, commodities, services, knowledge, amongst others. Globalization has dramatically impacted income inequality, altering the distribution of wealth within populations. The study seeks to shed light on globalization's impact on income distribution in different economic scenarios. Globalization in developed economies has caused labour-intensive industries to move to develop nations, leading to fewer job opportunities and stagnant wages for lower-skilled workers. Skilled workers have gained from global trade and technology, causing income gaps. Certain developed nations have successfully implemented inclusive policies to tackle income inequality, while others encounter difficulties in their practical implementation. Developing economies have benefited from globalization by accessing global markets and foreign investment. Still, they are also susceptible to external shocks and volatility, which can affect the financial stability of vulnerable populations. The article highlights the importance of customized strategies to tackle unique challenges encountered by diverse groups of nations. Developing economies should prioritize education, infrastructure, and social welfare investments to empower their workforce and support vulnerable communities. Developed economies should prioritize addressing job displacement and wage stagnation among low-skilled workers while leveraging technological advancements for broader advantages. The analysis emphasizes the need for global cooperation to tackle issues and create sustainable globalization. Collaboration can tackle income inequality and promote global prosperity.